Driving Decisions: The Impact of Environmental Factors, Brand Image, and Product Quality - Aditya Halim Perdana Kusuma Putra (Manunggal Halim Jaya, 2023)
This study aims to explore the effects of Environmental Factors, Brand Image, and Product Quality on the Purchase Decisions of Yamaha Fazzio motorcycles in Makassar City. Utilizing a questionnaire-based survey, data were collected from Yamaha Fazzio motorcycle consumers in Makassar City. The research employs multiple regression analysis as its methodological framework, with the questionnaire serving as the primary data collection tool. The population of this study encompasses Yamaha Fazzio motorcycle consumers in Makassar City, with the sample drawn using the Slovin's formula. The findings indicate that, based on partial tests, Environmental Factors, Brand Image, Product Quality, and Consumer Decisions have a positive and significant impact. Moreover, the results from the simultaneous tests reveal that Environmental Factors, Brand Image, and Product Quality collectively exert a significant and positive influence on Consumer Decisions.